Communication Patterns between Generations via Family WhatsApp Groups (Case Study: Amarta Family) - Halim, Dary (Jurnal Komunikasi dan Bisnis, 2024)
This research is inspired by the rapid development of the digital era which has shifted the place of communication from the real world to social media platforms, in this case the WhatsApp application, so that it has different patterns in each generation. Therefore, in analyzing the generations of WhatsApp group members, researchers tried to divide and classify family members into generation Y and generation Z according to their birth line. The aim of this research is to determine family communication patterns for each generation on the WhatsApp application. This research uses a descriptive qualitative approach. The subjects of this research are members of the Amarta family who are members of the family WhatsApp group. The sampling technique was purposive sampling and direct interviews. The research results show that there is a unique communication pattern in the WhatsApp Family group, each generation has the same communication pattern, namely the star pattern where each generation communicates, and each group member is free to talk and provide feedback. without any restrictions. or persuasive actions from generation Y and generation Z.